The Impact of the Existence of the Gunung Panggung Tuban Final Waste Disposal Site (TPA) on the Socio-Economic Conditions of the Surrounding Community - Siti Mutmainnah (Program Studi S1 Pendidikan IPS, Universitas Negeri Surabaya, 2026)
The existence of the Gunung Panggung Tuban Final Waste Disposal Site (TPA) as part of the regional waste management system has the potential to impact the social and economic life of the surrounding community. This study aims to analyze the impact of the Gunung Panggung Tuban Final Waste Disposal Site on the social and economic conditions of the surrounding community, as well as to determine the relevance of the research results to social studies learning as a contextual learning resource. This study used a quantitative approach with a survey method. The research sample consisted of 174 respondents determined through a probability sampling technique with multi-stage sampling, namely grouping (cluster sampling) based on the radius of residence from the landfill and proportional sampling in each zone (Proportionate Stratified Random Sampling). Data were collected using a Likert-scale questionnaire and analyzed using simple linear regression and One-Way ANOVA. The results of the study indicate that the existence of the Gunung Panggung Tuban Landfill significantly affects the social and economic conditions of the surrounding community. The effect on social conditions is negative with a regression coefficient of -0.367, indicating that an increase in the intensity of the landfill's existence is followed by a decrease in environmental comfort and the quality of social interactions in the community. Conversely, the effect on economic conditions is positive with a regression coefficient of 0.501, indicating an increase in job opportunities and additional income for some people. The results of the One Way ANOVA test show that there are significant differences in social conditions between residential zones (sig. 0.000), especially between Zone A and Zone B and Zone C, but there are no significant differences in economic conditions between zones. This finding is relevant to social studies learning as a contextual learning resource for the material on social change and environmentally based economic activities.